O planejamento e a estrutura organizacional no processo de contratação de bens e serviços nas Universidades Federais do Maranhão (UFMA) e de Santa Maria (UFSM) - Amorim, Ronaldo José (2014)
This work approaches the restrictive factors that interfere in the optimization of the planning of the process of recruiting of goods and services between the sectorial demand and the service of the request for the Unit of Administration in two Federal Universities. The theme is discussed found in the authors' visions as Etzioni (1967), Barnard (1968), Tironi et al (1991), Tofler (2003), Mintzberg (2004), Senge (2005), Matus (2006), Marchi and Wittmann (2008), Motta (2010), Baily et al. (2010), Morin (2011), Tridapalli, Fernandes and Machado (2011), Morgan (2011), Juran (2011), Dias e Costa (2012), Drucker (2012), among others. The protected concepts for the authors allow to notice new possibilities for the administration of the process of recruiting of goods and services in our organizations in times of changes. The objective of the research consists of analyzing the restrictive factors that interfere in the optimization of the planning of the process of recruiting of goods and services between the sectorial demand and the service of this request for the Unit of Administration in the Federal Universities of Maranhão (MA) and Santa Maria (RS). This case study has character exploratory, descriptive, of qualitative nature. They were accomplished 12 (twelve) interviews that made possible the collection and the analysis of the data, the method of the analysis of the interviewees' speech was used to reveal problems associated to planning, the organizational structure, that interferes in the planning of the process of recruiting of goods and services. The results reveal that the researched organizations maintain inadequate organizational structures. The unit of central planning guides the dissociated expense of the reality of the administration of the sectorial units.